Isolation and identification of Yersinia enterocolitica in bovine milk samples of bulk tanks from dairy farms in São Paulo, Brazil - Bertolini, Amanda Bezerra [UNESP]; Dutra, Marcelo Augusto Orsi [UNESP]; Guiraldi, Lívia Maísa [UNESP]; Dos Santos, Wesley José [UNESP]; De Medeiros, Maria Izabel Merino; Lucheis, Simone Baldini (Universidade Estadual de Londrina, 2019)
Milk and its derivatives are good substrates for the proliferation of pathogenic and quality-deteriorating microorganisms, demanding rigorous care with milking, processing, and storage. Among the various bacteria that can grow in raw refrigerated milk, Yersinia enterocolitica, is an invasive enteropathogen of humans. This bacterium can cause a number of intestinal and extraintestinal clinical symptoms, ranging from mild gastroenteritis to mesenteric lymphadenitis, similar to appendicitis. To evaluate the prevalence of pathogenic Yersinia enterocolitica in raw milk from bulk milk tanks located in the State of São Paulo, 102 bovine milk samples (one per dairy farm) were evaluated by microbiological analyses, followed by biochemical tests PCR and genetic sequencing. Microbiological testing did not isolate Y. enterocolitica. However, PCR analysis revealed six samples that were positive for Y. enterocolitica (5.9%), confirmed by genetic sequencing. Only the inv gene was detected, which is present in virulent and avirulent Y. enterocolitica strains. There was great difficulty in microbiological isolation due to the difficulty of competitiveness of Y. enterocolitica in a very rich microbiota of raw milk. Although virulence genes known to be present in potentially pathogenic strains of Y. enterocolitica have not been identified, the presence of this pathogen in milk from expansion tanks, identified through PCR and confirmed by genetic sequencing, suggests that Y. enterocolitica may be a risk to public health, especially if milk and its derivatives are consumed without heat treatment.
Keywords: Bovine milk; Microbiological analyses; Molecular diagnosis; Public health; Yersiniosis